Which European public sphere? - Tresch, Anke (Javnost (Ljubljana), 2012)
Since the beginning of the 1990s, the EU has been increasingly criticised for its democratic deficit, which is intrinsically linked to the absence of a public sphere at the European level. Whereas scholars consider the emergence of such a public sphere as a necessary requirement for the democratisation of the EU, they disagree on the conceptualisation and normative requirements for a meaningful public sphere at the European level. This article takes an empirical perspective and draws on the nation-state context of multilingual Switzerland to get insights into what a European public sphere might realistically look like. Based on a content analysis of the leading quality paper from each German- and French-speaking Switzerland by means of political claims analysis, it shows that three of the most often cited criteria for a European public sphere - horizontal openness and interconnectedness, shared meaning structures, and inclusiveness - are hardly met in the Swiss context. On this basis, it concludes that the normative barrier for finding a European public sphere might be unrealistically high and should be reconsidered.
Keywords: Europe; Evropa; javna sfera; javnost; democracy; demokracija